The role of the father in a modern family - Malina, Jolanta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The purpose of this article is to draw attention to the role of father in a family that changes over the years. Nowadays it is more and more common for fathers to leave their families. This is reflected in economic emigration and divorces. The lack of proper fathers’ involvement in playing the role of a father as well as raising children by single mothers has a negative impact on children’s development due to often difficult situations that mothers and their children can not cope with. Lack of a father in the family may, among others, cause the loss of the sense of security of its members, negatively affects the development of children. The article presents the results of research on women’s opinions about the role of father in a contemporary family.
Keywords: children; father's role; lack of father; sense of security